2019
DOI: 10.1200/jco.2019.37.7_suppl.523
|View full text |Cite
|
Sign up to set email alerts
|

Excellent outcomes in bilateral testicular germ cell tumors over four decades.

Abstract: 523 Background: Bilateral testicular germ cell tumours (BTC) form a small minority of testicular cancer and detailed management data are sparse. Methods: Bilateral testicular cancer (BTC) patients managed at a single cancer centre were retrospectively analyzed. Synchronous BTC was defined as uni+contralateral presentation within 3 months. Patient characteristics, treatment and outcomes were collected. Kaplan-Meier method was used to calculate the overall survival (OS) and relapse-free survival (RFS). Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The rest were not specified. More recently in 2019, Lu et al [ 7 ] identified 11 patients out of 118 TGCT cases who presented with bilateral tumors of discordant histology. Since then, a handful of individual cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The rest were not specified. More recently in 2019, Lu et al [ 7 ] identified 11 patients out of 118 TGCT cases who presented with bilateral tumors of discordant histology. Since then, a handful of individual cases have been reported.…”
Section: Discussionmentioning
confidence: 99%